Pengaruh External Pressure, Rationalization dan Nature of Industry terhadap Financial Statement Fraud - Sudarmadi Sudarmadi; Nabilah Dinda Oktaviani (AKUNTANSI 45, 2026)
This study aims to analyze the effect of external pressure, rationalization, and nature of industry on financial statement fraud, both partially and simultaneously. This research is quantitative in nature. The sample was obtained using a purposive sampling technique, resulting in 11 samples within the 2020–2024 period. The data used in this study were derived from financial statements. The tests employed in this research include descriptive statistical analysis, panel data regression model selection, classical assumption tests, and hypothesis testing. Data analysis was conducted using eviews 12 software. The results of the study indicate that, partially, external pressure and rationalization have no significant effect on financial statement fraud, while the nature of industry has a significant effect. Furthermore, the simultaneous test shows that external pressure, rationalization, and nature of industry influence financial statement fraud.